Pengaruh Emosional Terhadap Kinerja Pegawai - Yuniarti Yuniarti (UIN Antasari Banjarmasin, 2015)
his research aims: this research done with purpose to describe: 1 employees description emotional secretariat city banjarbaru regions .2 ) description of the employee performance secretariat city banjarbaru regions . 3 ) influence emotionally against the employee performance secretariat city banjarbaru regions. This research using correlational approach namely: give a description of the influence of emotional against the employee performance secretariat city banjarbaru regions . Samples of being respondent in this research is to use sampling techniques total where whole populations into the study sample which totaled 40 ( forty ) person employees in secretariat city banjarbaru regions especially the common section 31 And parts of community and social wealth 9 people. The result showed that emotional: influential significantly on variables the employee performance . Of statistical testing can be seen that t count & gt; t a table ( 2.756& gt; 2.035 ) of these calculations it can be seen that t count be outside the range -2.035 and 2.035 or significance smaller than 0.05.